Upaya Penanganan Lembaga Alternatif Penyelesaian Sengketa Terhadap Otoritas Jasa Keuangan, Pitriya Nur Habibah dan Devi Siti Hamzah Marpaung - Habibah, Pitriya Nur; Hamzah, Devi Siti (Jurnal Panorama Hukum, 2021)
The Financial Services Authority (OJK) is an independent institution that is free from interference from other parties or institutions. This institution has the functions, duties, and authorities of regulation, supervision, examination, and investigation. OJK was established under Law No. 21 of 2011 with the function of implementing an integrated regulatory and supervisory system for the entire financial services sector. The establishment of OJK with the need to restructure the institutions that carry out regulatory and supervisory functions in the financial services sector. The supervisory system carried out by the OJK is an integrated supervision system, meaning that all financial service activities carried out by various financial institutions are subject to the OJK regulatory and supervisory system. Alternative Dispute Resolution Institutions (LAPS) in the Financial Services Sector number 1/POJK.07/2014 which regulates Alternative Dispute Resolution Institutions in the Financial Services Sector. Dispute resolution must be carried out at the LJK in the OJK Regulation concerning Consumer Protection in the Financial Services Sector, which stipulates that each LJK must have a work unit and/or function as well as a service mechanism and settlement of complaints for consumers. If the dispute resolution at the LJK does not reach an agreement, the consumer can settle the dispute out of court or through the court. Out of court dispute resolution is carried out through the Alternative Dispute Resolution Institution (LAPS).